Chromium phosphonate metal organic framework material as well as solvent-free preparation method and application thereof

Through the solvent-free preparation method, the safety hazards and waste liquid problems of traditional solvent-thermal method in the preparation of high-proton conductive MOFs materials are solved, and the stability and proton conductivity of the material are realized, which is suitable for proton conductive applications.

CN119570050AActive Publication Date: 2025-03-07TIANJIN POLYTECHNIC UNIV

Patent Information

Application Number
CN202411502323.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-07
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

In the prior art, when preparing high-proton conductive MOFs materials, there are problems such as the use of organic solvents, harsh reaction conditions and the occurrence of large amounts of waste liquid.

Method used

Using the solvent-free preparation method, terephthalidine acid and chromium chloride hexahydrate were mixed and ground, and then heated, spontaneously cooled and washed with ethanol, and finally obtained the chromium phosphonate metal organic framework material by vacuum drying.

Benefits of technology

It has achieved solvent-free preparation, the material has the advantages of good stability and high proton conductivity, simple process, green and environmentally friendly, and is suitable for proton conductivity applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570050A_ABST
    Figure CN119570050A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of crystalline materials, and particularly relates to a chromium phosphonate metal organic framework material as well as a solvent-free preparation method and application thereof. The chemical formula is [Cr (H2BPD) 1.5]. The preparation method comprises the following steps: mixing an organic ligand p-phenylene diphosphonic acid and chromium chloride hexahydrate, grinding, carrying out a heating reaction, after the reaction is completed, spontaneously cooling to room temperature, repeatedly washing with ethanol until a supernatant is in a colorless and transparent state, and carrying out vacuum drying to obtain the light green chromium phosphonate metal organic framework material. The chromium phosphonate metal organic framework material can be applied to proton conduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crystalline materials, and particularly relates to a chromium phosphonate metal organic framework material and a solvent-free preparation method and application thereof. Background Art

[0002] Metal-Organic Frameworks (MOFs) are made of metal ions or metal clusters connected to organic ligands through coordination bonds. As a new type of porous material, it has the characteristics of large specific surface area, high porosity, and adjustable pores, which makes it have broad application prospects in the fields of gas adsorption and separation, catalysis, fluorescence, and proton conductivity. At present, there are many studies on how to improve the proton conductivity of MOFs materials. Common methods include: introducing acidic guest molecules into the pores of MOFs, which is also the most commonly used method, but the introduced guest molecules lack interaction with MOFs, and guest molecules will leak after a period of time. The second method is to use a direct synthesis method to use materials with proton donors (such as acidic groups) as organic ligands to directly synthesize MOFs materials. Therefore, it is possible to try to use phosphonic acid groups with high proton density to synthesize new MOFs materials with high proton conductivity.

[0003] Compared with carboxylic acid ligands, phosphonic acid ligands are more likely to form strong chemical bonds with metal atoms. The chemical stability of phosphonic acid MOFs materials generally depends on the valence state of the metal ion. Monovalent metal phosphonates are highly soluble, and the solubility gradually decreases with the increase of the metal valence state. Divalent metal phosphonates have low solubility and can obtain single crystals by hydrothermal or solvothermal techniques, while trivalent and tetravalent metal phosphonates rarely crystallize because they are highly insoluble and tend to precipitate in the form of disordered layered materials. Tetravalent metal phosphonates are insoluble even in strong acid solutions.

[0004] Cr-MOFs generally have good stability. Studies have shown that Cr-MOFs with sulfonic acid groups can exhibit high proton conductivity, but there are no reports on proton conduction of chromium phosphonate MOFs. In addition, with respect to chromium phosphonate MOFs, there is currently only one case reporting a method for synthesizing a chromium phosphonate skeleton using a two-step synthesis method, that is, first preparing a chromium-hydrogen bond organic framework (Cr-HOF), and then heating and dehydrating it to obtain the desired chromium phosphonate MOF. This method is significantly different from the solvent-free synthesis method used in the present invention.

[0005] Although the traditional solvothermal method is a common method for obtaining high-quality crystals, it still has the following shortcomings: (1) A large amount of organic reagents are required during the reaction, such as N,N-dimethylformamide and acetone. Their cost, toxicity and flammability make them a major safety hazard and easily lead to safety accidents.

[0006] (2) The reaction conditions are harsh. The solvothermal method usually needs to be carried out under high temperature and high pressure, and safety issues cannot be guaranteed.

[0007] (3) After the solvent thermal reaction is completed, a large amount of waste liquid is generated. The production of waste liquid will not only corrode the equipment, but also require extremely high costs for its treatment. Summary of the invention

[0008] In order to solve the above deficiencies and shortcomings of the prior art, the present invention provides a chromium phosphonate metal organic framework material and a solvent-free preparation method and application thereof.

[0009] The present invention is achieved through the following technical solutions: A chromium phosphonate metal organic framework material, the chemical formula of which is [Cr(H2BPD) 1.5 ], the ligand is terephthalic acid, and the structural formula is: ; The chromium phosphonate metal organic framework material has a three-dimensional network structure.

[0010] Furthermore, in the chromium phosphonate metal organic framework material, each chromium atom is connected to oxygen atoms on phosphate groups from six different ligands to form an octahedral structure; H2BDP 2- Each phosphonic acid group in the ligand connects two chromium atoms in a bidentate coordination mode. The above connection mode is infinitely extended in space to form a one-dimensional chain Cr-secondary building unit (Cr-SBU). Adjacent Cr-SBU chains are connected by the benzene ring of the ligand to form a three-dimensional network structure. In the three-dimensional network structure, there is a one-dimensional acid channel, in which the uncoordinated and ionized P-OH groups on the ligand are distributed. The present invention also provides a solvent-free preparation method of the chromium phosphonate metal organic framework material, comprising the following steps: The organic ligand terephthaloylphosphonic acid and chromium chloride hexahydrate are mixed and ground, and then heated for reaction. After the reaction is completed, it is spontaneously cooled to room temperature and repeatedly washed with ethanol until the supernatant is colorless and transparent. After vacuum drying, a light green chromium phosphonate metal organic framework material is obtained.

[0011] Furthermore, the molar ratio of the organic ligand terephthalenediphosphonic acid to chromium chloride hexahydrate is 1:1.

[0012] Furthermore, the specific operation of the heating reaction is as follows: using a programmed temperature increase method, setting the heating time to 30 minutes, heating to 150° C., and the reaction time is 24-48 hours.

[0013] Furthermore, the grinding was carried out in a glove box, the humidity was controlled at 15-20%, and the grinding time was 15 minutes.

[0014] Furthermore, the drying condition is: drying in a vacuum oven at 60° C. for 12 hours.

[0015] The invention also provides application of the chromium phosphonate metal organic framework material in proton conduction.

[0016] Beneficial technical effects of the present invention: The present invention adopts a grinding-solvent-free method to prepare a chromium phosphonate metal-organic framework material. The preparation method does not use an organic solvent, is green and environmentally friendly, and has a simple process. The prepared metal-organic framework crystal material has the advantages of good stability and high proton conductivity, so that the MOFs have potential applications in proton conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the XRD result of the material prepared in Example 1; Figure 2 This is a schematic diagram of the coordination structure of the material prepared in Example 1; Figure 3 This is a schematic diagram of the pore structure of the material prepared in Example 1; Figure 4 This is the infrared spectrum of the material prepared in Example 1; Figure 5 The SEM and EDS results of the material prepared in Example 1 are shown; Figure 6 This is a graph showing the thermogravimetric test results of the material prepared in Example 1; Figure 7 This is the XRD result of the material after high temperature treatment; Figure 8 This is a graph showing the impedance test results of the material prepared in Example 1; Among them, (a) is the result of impedance variation with temperature at 100% relative humidity; (b) The change of proton conductivity with temperature; (c) is the activation energy fitting result; (d) shows the change of conductivity with temperature at 80℃. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0019] Example 1 Weigh terephthalic acid (H4BPD) (238 mg, 1 mmol) and chromium chloride hexahydrate (CrCl3·6H2O) (266 mg, 1 mmol) and place them in 2 ml glass bottles respectively. Mix them in a glove box (humidity 15%) and grind them in a mortar for 15 minutes. Then transfer them into a 5 ml Teflon-lined stainless steel autoclave. Set the oven heating time to 30 min, heat to 150°C, and react for 24 h. Wash the product with anhydrous ethanol for at least three times until the supernatant is colorless after centrifugation. Dry them in a vacuum oven at 60°C for 12 hours to obtain the metal-organic framework crystalline material.

[0020] Example 2 Weigh terephthalic acid (H4BPD) (238 mg, 1 mmol) and chromium chloride hexahydrate (CrCl3·6H2O) (266 mg, 1 mmol) and place them in 2 ml glass bottles respectively. Mix them in a glove box (humidity 20%) and grind them in a mortar for 15 minutes. Then transfer them into a 5 ml Teflon-lined stainless steel autoclave. Set the oven heating time to 30 min, heat to 150°C, and react for 24 h. Wash the product with anhydrous ethanol for at least three times until the supernatant is colorless after centrifugation. Dry them in a vacuum oven at 60°C for 12 hours to obtain the metal-organic framework crystalline material.

[0021] Example 3 Weigh terephthalic acid (H4BPD) (238 mg, 1 mmol) and chromium chloride hexahydrate (CrCl3·6H2O) (266 mg, 1 mmol) and place them in 2 ml glass bottles respectively, mix them in a glove box (humidity 15%) and grind them in a mortar for 15 minutes, then transfer them into a 5 ml Teflon-lined stainless steel autoclave, set the oven heating time to 30 min, heat to 150°C, react for 48 h, wash the product with anhydrous ethanol at least three times until the supernatant is colorless after centrifugation, and dry them in a vacuum oven at 60°C for 12 hours to obtain the metal-organic framework crystalline material.

[0022] The characterization data of the materials obtained in Examples 1-3 are the same.

[0023] Example 1 was selected to obtain a powder of suitable size, and data was collected at 173K using a PANalytical X'Pert PRO high-resolution powder diffractometer. Data collection used Cu-Kα target rays monochromatized by a graphite monochromator. Absorption correction of the data was completed using SCALE3ABSPACK software. The crystal structure was obtained by direct analysis using the SHELXTL-97 program. The coordinates of all non-hydrogen atoms were first determined using the difference function method and the least squares method, and the hydrogen atom positions were obtained using the theoretical hydrogenation method, and then the crystal structure was refined using SHELXTL-97.

[0024] The molecular formula of the material is Cr(H2BPD)1.5, and the molecular weight is 406. From the perspective of skeleton connection construction, the crystal structure of the metal-organic framework belongs to the isometric crystal system, and the space group is P21 / c.

[0025] Characterization and analysis results of materials: Figure 1 The XRD diagram of the metal organic framework prepared in Example 1 is compared with the XRD diagram of the data fitting. The results show that the characteristic peaks of the two are completely consistent, indicating that the chromium phosphonate metal organic framework material is successfully prepared.

[0026] Figure 2 The coordination structure diagram of the chromium phosphonate metal organic framework material shows that: in the chromium phosphonate metal organic framework material, each chromium atom is connected to oxygen atoms on phosphate groups from six different ligands to form an octahedral structure; H2BDP 2- Each phosphonic acid group in the ligand connects two chromium atoms in a bidentate coordination mode. The above connection mode extends infinitely in space to form a one-dimensional chain-like Cr-secondary building unit (Cr-SBU). Adjacent Cr-SBU chains are connected by the benzene ring of the ligand, thereby forming a three-dimensional network structure.

[0027] Figure 3 The figure is a schematic diagram of the three-dimensional structure of the chromium phosphonate metal organic framework material. In the three-dimensional network structure, there is a one-dimensional acid channel, in which the uncoordinated and ionized P-OH groups on the ligand are distributed.

[0028] Figure 4 is the infrared spectrum of the chromium phosphonate metal organic framework material, located at 1203, 1160 and 1078 cm -1 The three new energy bands in the PO phase indicate that the oxygen atoms in P=O and PO are successfully coordinated with chromium.

[0029] Figure 5 The SEM and EDS images of the chromium phosphonate metal organic framework material show that the prepared metal organic framework crystals are block-shaped and have uniform particle size distribution.

[0030] Figure 6 is a thermogravimetric curve of the chromium phosphonate metal organic framework material, Figure 7 This is the XRD result of the material after high-temperature treatment, which shows that the prepared metal organic framework crystal has good thermal stability and can still maintain the stability of the framework at 420°C.

[0031] In order to obtain the proton conductivity of the chromium phosphonate metal organic framework, the following method was used for testing: Approximately 90 mg of MOF powder was placed in a custom-made mold under a pressure of 1000 kg cm -2 The resultant was pressed under pressure for 3 minutes to form a rectangular parallelepiped (about 0.2 × 0.4 × 1.0 cm 3 ) of the sample to be tested. Place two flat surfaces (0.2×0.4 cm 2 ) is fixed to the silver wire with silver conductive glue and sealed in a double-walled glass chamber. The temperature is controlled by temperature-controlled circulating water in the interlayer of the double-layer glass chamber. The humidity in the glass chamber is controlled by a series of saturated saline solutions. Then the impedance diagram of the sample to be tested is tested using an electrochemical workstation, with a frequency range of 1 Hz to 8 MHz and an AC potential of 100 mV. And its proton conductivity is calculated: L / RS (L=1cm, R is the impedance of the sample to be tested). The results are as follows Figure 8 Figure 8a shows that the conductivity of the prepared metal organic framework crystal can reach 1.44×10 −2 S / cm, up to 2.42×10 at 90°C − 2 S cm −1 ; It shows that the proton conductivity of the material is improved with the increase of temperature, and it has higher proton conductivity at high temperature. Figure 8b shows that the proton conductivity shows good stability with temperature changes, which means that the material can maintain its excellent proton conductivity over a large temperature range. This stability is very critical for high-temperature applications, especially in devices such as proton exchange membrane fuel cells. Figure 8c shows that the activation energy of proton conduction is only 0.1 eV, indicating that protons are very easy to conduct in this material, and low activation energy is a key factor for the material to conduct protons quickly. Generally, the lower the activation energy, the easier it is for protons to migrate in the material, and the better the conductivity. Figure 8d shows that the proton conductivity of the material can remain unchanged for at least 100 hours at 90°C and 100% relative humidity, without obvious attenuation, showing the excellent long-term stability of the material. This long-term stability is crucial for continuous operation in practical applications.

Claims

1. A chromium phosphonate metal organic framework material, characterized in that: The chemical formula is [Cr(H2BPD) 1.5 ], the ligand is terephthalic acid, and the structural formula is: ; The chromium phosphonate metal organic framework material has a three-dimensional network structure.

2. The chromium phosphonate metal organic framework material according to claim 1, characterized in that: In the chromium phosphonate metal organic framework material, each chromium atom is connected to oxygen atoms on phosphate groups from six different ligands to form an octahedral structure; H2BDP 2- Each phosphonic acid group in the ligand connects two chromium atoms in a bidentate coordination mode. The above connection mode extends infinitely in space to form a one-dimensional chain-like Cr-secondary building unit (Cr-SBU). Adjacent Cr-SBU chains are connected by the benzene ring of the ligand, thereby forming a three-dimensional network structure.

3. The chromium phosphonate metal organic framework material according to claim 2, characterized in that: In the three-dimensional network structure, there is a one-dimensional acid channel, in which the uncoordinated and ionized P-OH groups on the ligand are distributed.

4. A solvent-free preparation method of the chromium phosphonate metal organic framework material as claimed in any one of claims 1 to 3, characterized in that: The steps include: The organic ligand terephthaloylphosphonic acid and chromium chloride hexahydrate are mixed and ground, and then heated for reaction. After the reaction is completed, it is spontaneously cooled to room temperature and repeatedly washed with ethanol until the supernatant is colorless and transparent. After vacuum drying, a light green chromium phosphonate metal organic framework material is obtained.

5. The solvent-free preparation method of the chromium phosphonate metal organic framework material according to claim 4, characterized in that: The molar ratio of the organic ligand terephthalenediphosphonic acid to chromium chloride hexahydrate is 1:

1.

6. The solvent-free preparation method of the chromium phosphonate metal organic framework material according to claim 4, characterized in that: The specific operation of the heating reaction is as follows: using a programmed temperature increase method, setting the temperature increase time to 30 minutes, raising the temperature to 150° C., and the reaction time is 24-48 hours.

7. The solvent-free preparation method of the chromium phosphonate metal organic framework material according to claim 4, characterized in that: The grinding was carried out in a glove box with the humidity controlled at 15-20% and the grinding time was 15 minutes.

8. The solvent-free preparation method of chromium phosphonate metal organic framework material according to claim 4, characterized in that: Drying conditions: drying in a vacuum oven at 60°C for 12 hours.

9. Use of the chromium phosphonate metal organic framework material according to any one of claims 1 to 3 in proton conduction.

Citation Information

Patent Citations

  • Mesoporous functional hybrid material as well as preparation method and application thereof

    CN108067304A

  • Hydrogen bond organic framework material with ultrahigh proton conductivity as well as preparation method and application of hydrogen bond organic framework material

    CN117624629A

  • Chromium-based metal organic framework material synthesized by solvent-free method as well as preparation method and application of chromium-based metal organic framework material

    CN118085316A

  • Chromium phosphonate metal-organic frameworks, process for preparing the same and uses thereof

    US20240317785A1

Cited By

  • Method for preparing aminocapronitrile by ammonolysis of caprolactam

    CN121342688A